Desarrollo del autoestima de los niños a través del teatro y sus expresiones - Arias García, Evelyn Alexandra (2024)
The purpose of the research entitled “Development of children's self-esteem through theater and its expressions” is to explore in depth the role of theater and its expressions in the development of self-esteem in children, focusing on its application in the educational environment of the Unidad Educativa Pensionado Americano “International School” of the Riobamba canton. With a design based on grounded theory and a qualitative approach, an inductive method was used to observe and have a direct interaction with the subjects of study in their natural context. The population studied included 10 students in the sixth year of General Basic Education. Participant observation and focus group techniques were used to collect data, recording interactions, emotional expressions and behaviors during the theater sessions, as well as perceptions and experiences of the participants. The findings show that theater is a powerful pedagogical tool to promote self-expression, self-confidence and teamwork, which significantly contributes to the development of healthy self-esteem. This research highlights the underutilized potential of theater in education, proposing its integration into the school curriculum to promote children's emotional and social well-being.